PEMETAAN KONFLIK ANTARA PETERNAK AYAM BROILER DENGAN MASYARAKAT DI DESA KAYUPUTIH, KECAMATAN BANJAR, KABUPATEN BULELENG - Cendrawasih, Kadek; Hadi Tamim, Imron; Sudhana Astika, Ketut (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Kayuputih village is one of the dozen of villages by the number of large-scale farmers. In Kayuputih village of the many number of small to large sizedfarms, many found cage distance that is nit in accordance whit the Decree of the Directorate General of Animal Husbandry in 1993 No. 77 has been included, it is a farm with human settlements distance of at least 250 meters. This then raises problems because of the disruptionof the activities the society caused by air pollution because of the smell from the farm, environmental contamination caused by the disposal of waste from the farm of the river and the disruption of income traders caused by flies that constantly invade human. This research uses a qualitative approach to get a detailed depiction of conditions in the field. The theory used is the Triangle of Cinflict Galtung theory, this theory is an analytical tool to discover the attitudes, behavior and cntradictions between the farmers an society that underlie conflict. Conflict resolution has occurred used conflict governance system. Key Words: Farm Conflict, Galtung conflict Triangle, Conflict management